Anibal Quijano and his time - Valladares, Manuel (2019)
The article presents an overview on the personal, intellectual and political biography of Anibal Quijano. From his origins in Ancash, his early youth, his academic formation and his commitment to left-wing militancy. It examines his most outstanding proposals, from the Marxism, the theory of dependency and coloniality. It emphasizes Quijano’s coherence, from his ideological and political conception to his prolific sociological production, along his more notable contributions and studies.